Faktor – Faktor Yang Berhubungan Dengan Perkembangan Balita Usia 36-59 Bulan Di Bimba Star Kids Jakarta Timur Tahun 2025 - Samsiyah; Revinel; Meli Deviana (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Background: Delayed toddler growth and development remains a critical public health challenge in Indonesia, with a prevalence rate of approximately 30% in 2022. Risk factors such as history of Low Birth Weight (LBW), nutritional status, and maternal knowledge are suspected to play significant roles. Objective: This study aims to examine the relationship between BBLR history, nutritional status, and maternal knowledge level with the development of children aged 36-59 months. Methods: This quantitative research employed a cross-sectional design involving 80 respondents selected through total sampling at Bimba Star Kids in East Jakarta in 2025. Data were collected using questionnaires and KPSP instruments, then analyzed using Chi-Square test. Results: There was a significant association between LBW history and child development (p=0.008), but no significant correlation was found for nutritional status (p=0.551) or maternal knowledge (p=0.887). Conclusion: BBLR history is a critical risk factor for developmental delays, emphasizing the need for early screening and specific interventions to mitigate its impacts. Keywords: development, nutritional status, knowledge, KPSP.   Abstrak Latar Belakang: Masalah keterlambatan tumbuh kembang balita masih menjadi tantangan kesehatan masyarakat di Indonesia, dengan angka kejadian sekitar 30% pada tahun 2022. Faktor risiko seperti riwayat Berat Badan Lahir Rendah (BBLR), status gizi, dan pemahaman ibu diduga berperan penting. Tujuan: Studi ini bertujuan mengkaji hubungan antara riwayat BBLR, status gizi, serta tingkat pengetahuan ibu terhadap perkembangan anak usia 36–59 bulan. Metode: Penelitian kuantitatif dengan desain cross-sectional ini melibatkan 80 responden yang dipilih melalui total sampling di Bimba Star Kids Jakarta Timur tahun 2025. Pengumpulan data menggunakan kuesioner dan instrumen KPSP, dianalisis dengan uji Chi-Square. Hasil: Terdapat hubungan signifikan antara riwayat BBLR dan perkembangan anak (p value = 0,008), tetapi tidak ditemukan korelasi bermakna pada status gizi (p value = 0,551) maupun pengetahuan ibu (p value = 0,887). Kesimpulan: Riwayat BBLR merupakan faktor risiko kritis bagi keterlambatan perkembangan, sehingga diperlukan skrining dini dan intervensi spesifik untuk mitigasi dampaknya. Kata kunci: perkembangan, BBLR, status gizi, pengetahuan, KPSP.